Pembinaan dan Pendampingan Mualaf Kota Padang - Yufni Faisol; Syofyan Hadi; Reflinaldi Reflinaldi; Syafrian Syafrian (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The coaching and mentoring activities for mualaf (converts) in Padang aim to enrich the understanding and practice of Islam for converts in aspects of faith, worship, muamalah, and economics. The first stage of the activity (26 October 2019) was coaching filled with the main material of tawhid, prayer, and reading the Qur'an. After the implementation of the first stage of activities, the team gave a 2-week break which was filled with mentoring. While the second stage (6 October 2019) was filled with a review of the development of understanding and practice of the first stage material. The team uses interactive dialogue, discussion, and controlled practice methods. Through this method, participants are taught to be strong in maintaining their faith. Participants are provided with theory and practice of prayer procedures and reading the Qur'an. Based on the observations made during the activity, it was seen that there was positive progress that showed an increase in participants' understanding of the procedures for praying and reading the Qur'an. The team also introduces patterns of social interaction and business opportunities in various industrial sectors, so that participants can achieve economic independence and be able to adapt in the community.